2007
DOI: 10.1088/0957-4484/18/29/295204
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of 27 bp–8 kbp DNA and immobilization of thiol-modified DNA using dielectrophoresis

Abstract: Dielectrophoretic trapping of six different DNA fragments, sizes varying from the 27 to 8416 bp, has been studied using confocal microscopy. The effect of the DNA length and the size of the constriction between nanoscale fingertip electrodes on the trapping efficiency have been investigated. Using finite element method simulations in conjunction with the analysis of the experimental data, the polarizabilities of the different size DNA fragments have been calculated for different frequencies. Also the immobiliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
83
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 52 publications
(131 reference statements)
11
83
0
Order By: Relevance
“…In a detailed discussion, these authors explained the relatively high specific polarizability of short DNA fragments as being caused by their mechanical stiffness since the persistence length of double stranded DNA is in this range with about 130-230 bp. 24,38 Above this size, specific polarizability was found to rise again, which FIG. 6.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In a detailed discussion, these authors explained the relatively high specific polarizability of short DNA fragments as being caused by their mechanical stiffness since the persistence length of double stranded DNA is in this range with about 130-230 bp. 24,38 Above this size, specific polarizability was found to rise again, which FIG. 6.…”
Section: Resultsmentioning
confidence: 85%
“…However, the identical concentrations of DNA of different lengths should result in different capacitance values since the polarizability of DNA per base pair is not a constant value. For example, Tuukkanen et al 24 reported a decreasing polarizability per base pair, for fixed frequencies, with increasing molecular weight up to around 5 kbp. In a detailed discussion, these authors explained the relatively high specific polarizability of short DNA fragments as being caused by their mechanical stiffness since the persistence length of double stranded DNA is in this range with about 130-230 bp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have demonstrated DNA manipulation and trapping, 4,14-18 reaching down to several tenths of base pair DNA length. 15,19,20 Analytical applications of DNA DEP have been early proposed by Washizu et al 14 and recent studies revived this approach exploiting the length dependency of DNA DEP for separation. For example, a field flow fractionation device for DNA was recently demonstrated by Lao et al 21 Moreover, both the separation of linear DNA by size 22 and DNA topoisomers 23 were demonstrated in gel-free environment.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 Dielectrophoresis refers to a nonlinear electrokinetic phenomenon 30 in which a force is exerted on a dielectric particle when it is subjected to a spatially nonuniform electric field. This kind of electrokinetic phenomenon has been widely used to manipulate spherical particles in microfluidics such as particle trapping, [31][32][33][34][35] separation, 16,[35][36][37][38][39][40][41] focusing, 14,18,35 and cell discrimination. 42,43 Previous numerical and experimental studies demonstrate that the DEP effect should be taken into account to study the electrokinetic transport of spherical particles where nonuniform electric fields are present.…”
Section: Introductionmentioning
confidence: 99%